Theranostic Contact Lens for Modulation and Detection of Viral Infection Richard Newell. (2017) - Mak, Wing Cheung; Cheung, Kwan Yee; Orban, Jenny; Lee, Chyan-Jang; Turner, Anthony P.F.; Griffith, May
Abstract: Ocular fluid is an extracellular fluid excreted from the tear gland. Several important markers from ocular fluid have been identified as having significant clinical diagnostic value for various diseases. The contact lens is disposable, relatively cheap and serves as a platform to obtain direct intimate contact with ocular fluid and is therefore an attractive and a promising platform for point-of-care diagnostic tests. Here, we present an entirely new concept of a wearable theranostic device, in the form of a contact lens (theranostic lens) with a dual-function hybrid surface, to modulate and detect a pathogenic attack by herpes simplex virus type 1 (HSV-1). The theranostic lenses were constructed using a Layer-by-Layer (LbL) surface engineering technique to produce a functional hybrid surface containing both an anti-HSV-1 polysulfonate compound and specific antibodies for viral detection. The resulting theranostic lenses retained good optically transparency and surface wettability, and were non-toxic towards human corneal epithelial cells (HCECs). We showed that the theranostic lenses could capture and concentrate interleukin-1α (IL-1α), which is upregulated during HSV-1 infection, using an artificial cornea model integrated with a microfluidic system mimicking tear flow. The theranostics lenses exhibited effective anti-HSV-1 activity and good analytical performance for the detection of IL-1α, with a limit of detection of 1.43 pg mL -1 and a wide linear range covering the clinically relevant region. Our strategy also tackles the major problems in tear diagnostics that are associated with the small volumes from tear sampling and the low concentration of biomarkers in these samples. This work offers a new paradigm for wearable, non-invasive healthcare devices combining diagnosis and protection against disease. We believe that this approach holds promise as a next-generation, point-of-care and de-centralized diagnostic/theranostic platform for a range of biomarkers.